(untitled) (Comprehensive Journal of Science, 2025)
This research focuses on the phenomenon of blending (lexical compounding) as one of the important morphological mechanisms in generating vocabulary in the Arabic language. It compares its use in both Classical Arabic and the Libyan dialect. The study is based on the idea that Arabic is a dynamic and evolving language whose growth is driven by the needs of its speakers, and that blending serves as an effective method for abbreviation and expressing complex meanings in a single word. The research highlights the contributions of early linguists, such as Al-Khalīl and Sibawayh, in establishing the concept, and then shows how it developed among modern scholars due to the increasing need to create new terminology. The study also emphasizes the linguistic significance of the Libyan dialect, particularly the Bedouin variety, as it is considered one of the closest dialects to Classical Arabic, retaining ancient phonetic and morphological features, which makes it a rich field for studying blending. In addition, the research explains the impact of environment, cultural traditions, and heritage on the formulation of blended terms with particular meanings. Thus, it concludes that blending is not merely a linguistic phenomenon, but rather a tool for linguistic innovation, cultural identity preservation, and for keeping pace with scientific, social, and technological changes.